Persepsi Wisatawan Nusantara Terhadap Kawasan Sanur Sebagai Destinasi Pariwisata Berkelanjutan - Sari, Desak Gede Venia Monika; Dianasari, Dewa Ayu Made Lily; Suasapha, Anom Hery (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
The Sanur area is a tourism destination that has developed rapidly in Denpasar City. Tourism in the Sanur area has implemented sustainable tourism but is still weak in environmental management. This study aims to determine the perceptions of domestic tourists towards the Sanur area as a sustainable tourism destination. The number of respondents to this study was 100 respondents from domestic tourists who had been to the Sanur tourism area. This study uses a quantitative descriptive analysis technique, with a scale of measurement using a Likert scale. The results showed that the perception of domestic tourists towards the Sanur area as a sustainable tourism destination had positive ecological impacts with the highest average score of 4.41, namely tourism in the Sanur area increased awareness of the importance of preserving local natural resources. The negative ecological impact with the highest average value is 2.88, namely tourism in the Sanur area increases environmental problems. Tourist perceptions of positive economic impacts with the highest average value of 4.43, namely tourism in the Sanur area can create new markets for local products and negative economic impacts with the highest average value of 3.55, namely the development of tourism in the Sanur area increases taxes on use properties. Domestic tourists' perceptions of positive social impacts with the highest average score of 4.43, namely tourism development in the Sanur area provide opportunities for tourists to participate in cultural activities. And for the negative impact with the highest average value of 3.17, namely the development of tourism in the Sanur area resulting in density in public places.